Displasia renal em cães: estudo retrospectivo (2008-2013) - Lima, Samara Rosolem; da Silva, Leilane Aparecida; Dias, Geovanny Bruno Gonçalves; Lopes, Letícya Lerner; da Cruz, Raquel Aparecida Sales; Sonne, Luciana; Pescador, Caroline Argenta; Colodel, Edson Moleta (Acta Scientiae Veterinariae, 2017)
Background: Renal dysplasia, which has been reported in some dogs and human patients, refers to a developmental disorder of renal parenchyma due to imperfect inductive interaction between the mesonephric duct and the metanephric blastemal. In dogs, the characteristic histological findings on which diagnosis is based include (1) persistent metanephric ducts surrounded by primitive mesenchyme, (2) fetal or immature glomeruli, (3) fetal or immature tubules, and (4) anomalous presence of interstitial fibrous tissue. The aim of this study was to report the major pathological and immunohistochemical features of nine young dogs necropsied with renal dysplasia. Cases: The necropsy files from the Laboratório de Patologia Veterinária (LPV) of the Universidade Federal do Mato Grosso (UFMT) were reviewed between the years 2008 and 2013. Dogs diagnosed with chronic kidney failure and macroscopic and histopathological renal lesions consistent with renal dysplasia were selected. Kidney fragments in paraffin blocks were cut and stained with hematoxylin and eosin and by immunohistochemistry (IHC) using anti-vimentin and anti-cytokeratin monoclonal antibodies. The staining was considered positive for the presence of at least one renal cell marked with brown cytoplasmic staining clear and unambiguous. A total of 787 necropsies of dogs were performed. Of these, 64 had a clinical diagnosis of chronic renal failure of which 9 were classified as renal dysplasia. The age of the dogs ranged from 3 months to 2 years. Clinical signs were characterized by anorexia and non-regenerative anemia in 88.9%, vomiting 66.7%, dehydration 55.6%, uremia 55.6%, convulsion 33.4%, abdominal pain 22.3% and diarrhea in 11.2% of cases. At necropsy the main macroscopic changes in the kidneys were external surface with pale staining, in 6 of 9 dogs necropsied. Additionally, 5 dogs, cystic cavities of various sizes from 0.1 to 5 cm in diameter, diffusely distributed in the renal subcapsular surface and cutting were observed. Of the 64 dogs with diagnosis of chronic renal failure, 14.06% had dysplastic kidney changes, characterized by dilatation of Bowman’s space, glomerular and tubular atrophy, immature glomeruli and tubules, lymphocytic interstitial inflammation and fibrosis. In the dogs with renal dysplasia, it was observed that the tubular structures showed marked glomerular labeling for vimentin. Moreover, the kidneys of normal dogs showed weak or absent for marking tubes and glomerular structures for vimentin, and strong staining for cytokeratin in tubular cells, glomerular cells and collecting ducts. Discussion: Renal morphological damage observed in these nine dogs less than two years old, that contained degenerative and inflammatory changes, fibrosis and glomerular atrophy, but mostly immature glomeruli and tubules were associated with atypical renal dysplasia. This condition develops when the urethral diverticulum and metanephric blastoma not properly form in the embryonic stage, resulting in abnormal metanephric differentiation and formation of structures that do not recapitulate the normal nephrogenesis. Abnormal kidney function in young animals caused chronic renal failure resulting in death. The results of immunohistochemical observed in this study can complement the diagnosis of renal dysplasia. The morphological normality can be observed in the proportion of mesenchymal and epithelial tissue in the different structures of the kidney by staining with anti-cytokeratin and anti-vimentin. In the present study, there was moderate to strong labeling of vimentin in glomerular and tubular structures being dysplastic kidney would be expected to occur in normal dogs predominant staining with cytokeratin. Based on the clinic, pathological and immunohistochemical findings it is concluded that the animals developed renal dysplasia.